2020
DOI: 10.1016/j.kint.2020.02.039
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance favoring follicular helper T cells over IL10+ regulatory B cells is detrimental for the kidney allograft

Abstract: A high frequency of regulatory B (Breg) cells, generally transitional B cells, has been associated with long-term kidney allograft survival and operational tolerance. However, circulating follicular helper T cells (cTfh) correlate with graft rejection. In order to better understand the interplay between these cell subsets and to determine their association with graft outcome we studied transitional and IL10 D Breg cells, as well as cTfh, pre-and posttransplantation in a prospective cohort of 200 kidney transpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 39 publications
(53 reference statements)
2
9
1
Order By: Relevance
“…Activated CD24 + CD38 + transitional B cells yielded minimal TNFa + IL-10cells (<0.5%) but gave rise to the highest proportion of IL-10 + TNFacells (~10%) amongst all B cell subsets (Figure 4D-E, S11). This aligns with prior reports indicating transitional B cells had greater regulatory effects on conventional CD4 + T cells than naïve or memory B cells (Nova-Lamperti et al 2016;Shabir et al 2015;Newell et al 2010;Cherukuri et al 2014Cherukuri et al , 2017Cherukuri et al , 2021Hasan et al 2019;Laguna-Goya et al 2020). Activation of naïve B cells yielded relatively few TNFa + or IL-10 + cells, such that most cells did not produce either cytokine (~92%) (Figure 4D-E, S11).…”
Section: Conventional Breg Immunophenotypes Capture Few Il-10-producing B Cells and Enrich For Pro-inflammatory Cytokinessupporting
confidence: 91%
See 1 more Smart Citation
“…Activated CD24 + CD38 + transitional B cells yielded minimal TNFa + IL-10cells (<0.5%) but gave rise to the highest proportion of IL-10 + TNFacells (~10%) amongst all B cell subsets (Figure 4D-E, S11). This aligns with prior reports indicating transitional B cells had greater regulatory effects on conventional CD4 + T cells than naïve or memory B cells (Nova-Lamperti et al 2016;Shabir et al 2015;Newell et al 2010;Cherukuri et al 2014Cherukuri et al , 2017Cherukuri et al , 2021Hasan et al 2019;Laguna-Goya et al 2020). Activation of naïve B cells yielded relatively few TNFa + or IL-10 + cells, such that most cells did not produce either cytokine (~92%) (Figure 4D-E, S11).…”
Section: Conventional Breg Immunophenotypes Capture Few Il-10-producing B Cells and Enrich For Pro-inflammatory Cytokinessupporting
confidence: 91%
“…Prior studies established that human IL-10 + peripheral B cells co-express the proinflammatory cytokines TNFa and IL-6 (Lighaam et al 2018;Cherukuri et al 2014), and that transitional B cells have a higher ratio of IL-10:TNFa. These observations coincided with the finding that transitional B cells demonstrate significantly enhanced immunoregulatory activity on CD4 + T cells as compared to other stimulated B cell subsets, suggesting that IL-10:TNFa ratios reflect a meaningful metric of immunoregulatory capacity (Nova-Lamperti et al 2016;Shabir et al 2015;Newell et al 2010;Cherukuri et al 2014Cherukuri et al , 2017Cherukuri et al , 2021Hasan et al 2019;Laguna-Goya et al 2020). In the present study, we observed that transitional B cells were the only subset with a positive IL-10:TNFa log ratio amongst B cell subsets, suggesting that the immunoregulatory potential of B cells is diminished upon maturation and differentiation.…”
Section: Il-10-producing B Cells Potential Is Increased In Operationally Tolerant Liver Allograft Recipientssupporting
confidence: 81%
“…Our data agree with reports of others describing higher total and/or IL10+ Breg numbers in HC compared to patients with nephropathy/dialysis 23–26 or transplant recipients, 25,27–31 and transplant recipients pretransplant as compared to posttransplant. Our data disagree with reports describing similar Breg numbers in ESRD patients and HC 32–34 …”
Section: Discussioncontrasting
confidence: 99%
“…Laguna-Goya et al. reported that the reduction in tBregs and IL-10 + tBregs is positively associated with acute rejection after kidney transplantation ( 14 ). However, Zhou et al.…”
Section: Introductionmentioning
confidence: 99%